IL‐32θ negatively regulates IL‐1β production through its interaction with PKCδ and the inhibition of PU.1 phosphorylation. Issue 17 (1st July 2014) - Kim, Man Sub; Kang, Jeong-Woo; Lee, Dong Hun; Bak, Yesol; Park, Yun Sun; Song, Yong-Seok; Ham, Sun Young; Oh, Deok Kun; Hong, Jintae; Yoon, Do-Young
Abstract : It has been well known that IL‐32 exerts pro‐inflammatory effects on the various inflammatory diseases in clinical studies. Here, we confirmed that IL‐32θ, a new isoform of IL‐32, decreased the phorbol 12‐myristate 13‐acetate (PMA)‐induced IL‐1β expression in THP‐1 human myelomonocyte. We previously reported that the IL‐32 isoforms control expressions of other cytokines via novel PKCs. Likewise, IL‐32θ interacted with PKCδ, and consequently inhibited PKCδ‐mediated phosphorylation of PU.1. Moreover, IL‐32θ attenuated the localization of PU.1 into the IL‐1β promoter region. These findings reveal that IL‐32θ reduces PKCδ‐mediated phosphorylation of PU.1, resulting in attenuation of IL‐1β production. Abstract : IL‐32θ attenuates IL‐1β production. IL‐32θ interacts with PKCδ and PKCε. The association with PKCδ and IL‐32θ inhibit PKCδ‐mediated PU.1 activation.